The tumor immune microenvironment of nasopharyngeal carcinoma after gemcitabine plus cisplatin treatment - Lv, Jiawei; Wei, Yuan; Yin, Jian-Hua; Chen, Yu-Pei; Zhou, Guan-Qun; Wei, Chen; Liang, Xiao-Yu; Zhang, Yuan; Zhang, Cui-Juan; He, Shi-Wei; He, Qing-Mei; Huang, Zhuo-Li; et al. (Nature medicine, 2023)
Gemcitabine plus cisplatin (GP) chemotherapy is the standard of care for nasopharyngeal carcinoma (NPC). However, the mechanisms underpinning its clinical activity are unclear. Here, using single-cell RNA sequencing and T cell and B cell receptor sequencing of matched, treatment-naive and post-GP chemotherapy NPC samples ( n = 15 pairs), we show that GP chemotherapy activated an innate-like B cell (ILB)-dominant antitumor immune response. DNA fragments induced by chemotherapy activated the STING type-I-interferon-dependent pathway to increase major histocompatibility complex class I expression in cancer cells, and simultaneously induced ILB via Toll-like receptor 9 signaling. ILB further expanded follicular helper and helper type 1 T cells via the ICOSL–ICOS axis and subsequently enhanced cytotoxic T cells in tertiary lymphoid organ-like structures after chemotherapy that were deficient for germinal centers. ILB frequency was positively associated with overall and disease-free survival in a phase 3 trial of patients with NPC receiving GP chemotherapy ( NCT01872962 , n = 139). It also served as a predictor for favorable outcomes in patients with NPC treated with GP and immunotherapy combined treatment ( n = 380). Collectively, our study provides a high-resolution map of the tumor immune microenvironment after GP chemotherapy and uncovers a role for B cell-centered antitumor immunity. We also identify and validate ILB as a potential biomarker for GP-based treatment in NPC, which could improve patient management. Analysis of tumor samples from patients with nasopharyngeal carcinoma shows that gemcitabine plus cisplatin chemotherapy activates a unique population of innate-like B cells, which enhance the cytotoxic CD8 + T cell response and are associated with better clinical outcomes.